Optical heart rate monitoring in competitive swimming - an agreement study - Goebe, L. M.; Schneider, C.; Toerpel, A.; Ferrauti, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In many sports, heart rate (HR) monitoring is used to quantify internal training load and to control and steer exercise intensity [1]. In swimming, the standard method of ECG-based HR recording is error-prone, as chest straps may slip during swimming and wall push-offs, especially when no swim suit is worn. The optical HR sensor Verity Sense (VS) by Polar may overcome the practical limitations of chest straps due to fixation on the swimming goggles. In this study [2], we evaluate the agreement between the VS and Polar H10 chest strap sensors during swimming.